2005
DOI: 10.1063/1.1888325
|View full text |Cite
|
Sign up to set email alerts
|

Dual-frequency capacitive discharges: Effect of low-frequency current on electron distribution function

Abstract: In low-pressure dual-frequency capacitive discharges, the effect of the low-frequency current on the electron distribution function (EDF) was investigated through the particle-in-cell simulation with Monte Carlo collision model. As the low-frequency (2MHz) current increases for the fixed high-frequency (27MHz) current, the EDF changes from Druyvesteyn to bi-Maxwellian (in the absence of secondary electron emission) or Maxwellian type (in case with secondary electron emission), along with the significant drop i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 29 publications
3
22
1
Order By: Relevance
“…Various physical mechanisms produce coupling between the two frequencies, and these effects have been explored in general terms in a number of recent papers, e.g. [1,2,3,4,5,6]. The purpose of the present paper is to discuss the electron heating mechanisms that operate in dual-frequency discharges-in particular, to elucidate their nature and significance, and as far as possible supply convenient formulae that may be used as elements in a comprehensive theoretical understanding of these discharges.…”
Section: Introductionmentioning
confidence: 99%
“…Various physical mechanisms produce coupling between the two frequencies, and these effects have been explored in general terms in a number of recent papers, e.g. [1,2,3,4,5,6]. The purpose of the present paper is to discuss the electron heating mechanisms that operate in dual-frequency discharges-in particular, to elucidate their nature and significance, and as far as possible supply convenient formulae that may be used as elements in a comprehensive theoretical understanding of these discharges.…”
Section: Introductionmentioning
confidence: 99%
“…19 Kim and Lee also reported that the EEDF evolves from Druyvesteyn to bi-Maxwellian as the rf frequency increases from 2 to 27 MHz. 20 Seo et al 21 and Gudmundsson 22 also reported that the EEDF in a planar inductive discharge appears to be Maxwellian at low pressures and evolves into a Druyvesteyn-like distribution at high pressures. Moreover, a careful account of the effect of the high-energy tail of Maxwellian distribution 23 often results in substantially higher rates of collision 24 and kinetic energy losses as compared with the Druyvesteyn-like distribution.…”
Section: Introductionmentioning
confidence: 92%
“…10 Because ion bombardment energies are determined mainly by the structures and parameters of dual rf-biased sheaths, we must pay attention to the sheath dynamics within a dual frequency configuration. Assuming the current density and electric field to be sinusoidal, Kim et al 8 studied the effect of low frequency current on the electron distribution by using the PIC/MC method. With simplified models, some authors obtained analytical expressions for dual frequency-biased sheaths.…”
Section: Introductionmentioning
confidence: 99%